Selank Administration Affects the Expression of Some Genes Involved in GABAergic Neurotransmission - Volkova, Anastasiya; Shadrina, Maria; Kolomin, Timur; Andreeva, Lyudmila; Limborska, Svetlana; Myasoedov, Nikolay; Slominsky, Petr (Frontiers in Pharmacology, 2016)
Clinical studies have shown the similarity of the spectrum of physiological effects of Selank and classical benzodiazepines, such as diazepam and phenazepam. These data suggest that there is a similar basis of their mechanism of action. To test this hypothesis we studied the effect of Selank and GABA on the expression of genes involved in the neuroreсeption and neurotransmission. We analyzed the expression of 84 genes involved in neuroreсeption (e.g., major subunit of the GABA receptor, transporters, ion channels, dopamine and serotonin receptors) in the frontal cortex of rats 1 and 3 hours after the administration of Selank or GABA (300 μg/kg) using real-time PCR method. We found significant changes in the expression of 45 genes 1 hour after the administration of the compounds. Three hours after Selank or GABA administration, 22 genes changed their expression. We found positive correlation between the changes in genes expression within 1 hour after administration of Selank or GABA. Our results showed that Selank caused a number of alterations in the expression of genes involved in neuroreсeption. The data obtained indicate that Selank is characterized by its complex effects on nerve cells, and one of its possible molecular mechanisms is associated with allosteric modulation of the GABAergic system.